Isolation of myelin basic protein from whole tissue extracts by selective pH-dependent solubilization - Guo, Kelin; Berlet, Hans (Preparative biochemistry & biotechnology, 1997)
A previous study1 of the selective solubility of myelin basic protein (MBP) of tissue extracts at pH 9.0 has raised issues of its quantitative recovery, and the differential solubility of its charge isomers. The pH-dependent solubility of proteins of acid extracts of delipidated tissue of bovine spinal cord was therefore reexamined. MBP of whole extracts was completely soluble up to pH 8.0 only, and less so by 25 % at pH 9.0, and 43 % at pH 10.0. The proteins other than MBP were virtually insoluble between pH 5.0 to 6.0, and 9.0 to 10.0. The solubility of the main charge isomers I to III of MBP of 18.5 kDa was found not to be affected by pH. Either pH 5.0 or 9.0 is therefore suitable for the selective isolation of MBP from whole tissue extracts, only pH 5.0 providing for the complete recovery of MBP. The pH-dependent solution behaviour was also examined following the separation of proteins of whole extracts by anion exchange chromatogra phy at pH 10.4. Purified MBP and several related minor cationic components of lower molecular weight were soluble throughout. In contrast, the anionic proteins were only partly soluble between pH 4.0 to 10.0, i.e. by 4 to 20%. The results are consistent with specific protein-protein interactions of the proteins of whole extracts, either enhancing the solubility of non-MBP proteins, e.g. at pH 7.0, or impairing that of MBP between pH 8.0 to 10.0.